Depression Prevalence in Neuropathic Pain and Its Impact on the Quality of Life. (16th June 2020) - Cherif, Farah; Zouari, Hela G.; Cherif, Wissal; Hadded, Monia; Cheour, Majda; Damak, Rahma
Abstract : Introduction . The management of neuropathic pain remains complex, generally because of the psychiatric comorbidity that is often underdiagnosed. The objectives of our work were to determine the link between depression and the characteristics of NP on the one hand and quality of life on the other hand, in a sample of subjects consulting for neuropathic pain (NP) regardless of etiology. Methods . We conducted a cross-sectional study involving 61 neuropathic pain consulting patients in whom we assessed five parameters, namely, neuropathic pain based on DN4, pain intensity using EVA, anxiety, and depression according to the HADS and quality of life. Results . The study population mean age was 52.71 ± 14.29 years while the sex ratio (m/f) was 0.52. The neuropathic pain's most common etiologies were postherpetic pain, carpal tunnel syndrome, and diabetic neuropathy. Depression and anxiety prevailed by 65.6% and 73.7%, respectively. The quality of life was impaired with average SF-12 physical and mental scores of 33.76 ± 8.03 and 37.78 ± 11.52, respectively. The overall mean BPI score was 5.53 ± 1.76. Patients with high DN4 scores were significantly more depressed (p = 0.025 ). A significantly positive association was found between the depression score and the pain intensity (p = 0.001, r  = 0.41). Depressed subjects had a poor quality of life according to SF-12 and BPI. Conclusion . Given the depressive comorbidity impact on the neuropathic pain components as well as the quality of life, screening for this comorbidity should be part of the baseline ND assessment.